Seasonal variation of microplastics density in Algerian surface waters (South-Western Mediterranean Sea) - SETITI, SKANDER; HAMDI, BOUALEM; CHERNAI, SAFIA; HOUMA BACHARI, FOUZIA; BACHOUCHE, SAMIR; GHEZALI, YOUSRA; SUARIA, GIUSEPPE (Mediterranean Marine Science, 2021)
Coastal waters worldwide are widely contaminated with various-size plastics, whose presence in aquatic ecosystems has been shown to produce a wide range of economic and social impacts and harmful effects on marine ecosystems. While microplastics have been reported from many regions of the Mediterranean Sea, very few data exist regarding microplastics concentration inn Algerian waters. In this study, we used a Manta trawl (330 μm) at six sampling stations in Bou-Ismail Bay, Algeria (South-West Mediterranean Sea) in order to provide novel information about the occurrence and composition of microplastics along the Algerian coast. Sampling was performed seasonally at six different sampling stations in 2018, providing additional information about the spatio-temporal variability of microplastics concentrations at the sea surface. Microplastics were found in all collected samples, with highly variable concentrations of 0.95, 0.88, 1.26, and 0.36 items/m3 in Autumn, Winter, Spring and Summer, respectively, and an overall mean concentration of 0.86 ± 0.35 items/m3. A classification based on the shape and appearance of microplastics indicated the predominance of fibers (32%), followed by fragments (27%), films (16%), foams (13%), and granules (12%). A qualitative microplastics analysis through Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR) revealed that microplastics were mainly composed of polyethylene (68.2%), polypropylene (24.7%), polystyrene (4.1%) and other polymers (3%). These data provide an initial overview of the quantity, characteristics, and spatio-temporal distribution of floating microplastics in Bou-Ismail Bay (Algeria).